Metabolism of aildenafil in vivo in rats and in vitro in mouse, rat, dog, and human liver microsomes. Issue 6 (6th December 2013) - Li, Yan; Wu, Linan; Gu, Yuan; Si, Duanyun; Liu, Changxiao
<x xml:space="preserve">Abstract</x> Aildenafil, 1‐[3‐(6, 7‐dihydro‐1‐methyl‐7‐oxo‐3‐propyl‐1H‐pyrazolo [4, 3‐d] primidin‐5‐yl)‐4‐ethoxyphenyl] sulfonyl‐cis‐3, 5‐dimethylpiperazine, a phosphodiesterase type V enzyme inhibitor (PDE5I), is under development for treatment of erectile dysfunction (ED). The purpose of this study was to elucidate metabolism of aildenafil in vivo in rats and in vitro in mouse, rat, dog, and human liver microsomes. Thirty‐one phase I metabolites have been found by LTQ/Orbitrap hybrid mass spectrometry in rat urine, faeces, and bile after oral administration. Major biotransformation pathways of aildenafil included N‐dealkylation of the piperazine ring, hydroxylation and dehydrogenation, aliphatic hydroxylation and loss of alkyl group of piperazine ring. Minor pathways involved hydroxylation on the phenyl ring, pyrazole N‐demethylation, O‐deethylation, loss of piperazine ring (cleavage of N‐S bond) and dehydrogenation on the piperazine ring. Similar metabolic pathways of aildenafil were observed in the incubations of liver microsomes from mouse, rat, and dog as well as from human. The depletion rate of parent drug in mouse and rat liver microsomes was significantly different from that in human liver microsomes. The cytochrome P450 reaction phenotyping analysis was conducted using isozyme‐specific inhibitors. The results indicated that CYP3A was the main isoenzyme involved in oxidative metabolism of aildenafil. Overall, these in vitro and in vivo findings should provide valuable information on possible metabolic behaviours of aildenafil in humans. Copyright © 2013 John Wiley & Sons, Ltd.